2018
DOI: 10.1080/07399332.2018.1424168
|View full text |Cite
|
Sign up to set email alerts
|

Amniocentesis test uptake for congenital defects: Decision of pregnant women in Vietnam

Abstract: Our study aimed to identify the knowledge, attitude, and factors associated with uptake of amniocentesis test amongst pregnant women of advanced maternal age (35+ years old). A cross-sectional survey was performed on 481 participants in 2016. Women with higher educational attainment, higher income level, having a baby with congenital defects, and women with better knowledge and/or attitude about amniocentesis test were more likely to accept the test. Our study suggested the importance of counseling for women a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Evidence from our review indicates a dichotomy in which women with advanced educational backgrounds and those with secondary education or less are predisposed to opt for invasive diagnostic procedures. The first category is characterized by a better overall understanding of their available options [14,[16][17][18][19]28,29]. Conversely, the second category may be influenced by partial or misinformed perspectives on the invasive procedure, such as the risk of miscarriage [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from our review indicates a dichotomy in which women with advanced educational backgrounds and those with secondary education or less are predisposed to opt for invasive diagnostic procedures. The first category is characterized by a better overall understanding of their available options [14,[16][17][18][19]28,29]. Conversely, the second category may be influenced by partial or misinformed perspectives on the invasive procedure, such as the risk of miscarriage [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Education levels have been identified as critical variable. An array of studies has indicated a correlation between higher educational attainment and increased utilization of invasive prenatal testing [14,[16][17][18]28,29]. On the other hand, other studies report that invasive testing, as opposed to NIPT, was associated with lower educational background (p=0.023).…”
Section: Sociodemographic Characteristicsmentioning
confidence: 99%
“…From a socio-demographic and clinical-obstetric point of view, studies with different quality levels unanimously indicate that advanced maternal age (Beulen et al, 2015;Gil et al, 2015;Grinshpun-Cohen et al, 2015a, 2015bSchoonen et al, 2012;Ternby et al, 2015;Watanabe et al, 2017), having a risk for genetic anomalies and previous abortions induce women to undergo prenatal testing, without distinction between invasive or non-invasive test (Chan et al, 2014;Seven et al, 2017;Skutilova, 2015). Similarly, no differences emerge in the use of both invasive and noninvasive prenatal testing in relation to educational level, in particular a higher educational attainment is associated with a greater use of prenatal test in general (Bangsgaard and Tabor, 2013;Beulen et al, 2015;Canh Chuong et al, 2018;Dicke et al, 2014;Farrell et al, 2014;Gil et al, 2015). Only a study with poor methodological quality (Crombag et al, 2016) reports that women with a high level of education are more likely to decline cFTS.…”
Section: Discussionmentioning
confidence: 99%
“…Higher educational attainment is associated with a greater use of both invasive and non-invasive prenatal testing (Bangsgaard and Tabor, 2013;Beulen et al, 2015;Canh Chuong et al, 2018;Dicke et al, 2014;Farrell et al, 2014;Gil et al, 2015). In addition, the studies by Chan et al (2014) and by Cheng et al (2018) indicate that a low level of education is associated with the choice of invasive prenatal diagnosis rather than NIPT.…”
Section: Sociodemographic and Clinical Characteristicsmentioning
confidence: 99%
“…Pregnant women in Singapore are routinely offered to screen for Down Syndrome (DS). 1 The utilization of prenatal testing is associated with many factors including advanced maternal age, [2][3][4] family history of DS, 5 ethnicity, 3,4,6,7 education, 2-4,7-10 income, 10 gestational age, 11 inclination to terminate the pregnancy of an affected fetus, 4,12 religiosity, [13][14][15] conception method, and physician's recommendation. [16][17][18] Traditionally, pregnant women are offered a combined First Trimester Screening (cFTS) which includes ultrasonography and serum screening.…”
Section: Introductionmentioning
confidence: 99%